Lack of Blue Light Regulation of Antioxidants and Chilling Tolerance in Basil - Larsen, Dorthe H.; Li, Hua; Shrestha, Samikshya; Verdonk, Julian C.; Nicole, Celine C. S.; Marcelis, Leo F. M.; Woltering, Ernst J. (Frontiers in Plant Science, 2022)
Blue light, measuring from 400 to 500 nm, is generally assumed to increase the content of antioxidants in plants independent of the species. Blue light stimulates the biosynthesis of phenolic compounds such as flavonoids and their subclass anthocyanins from the phenylpropanoid pathway. Flavonoids, anthocyanins, and phenolic acids are strong reactive oxygen species (ROS) scavengers and may lessen the symptoms of abiotic stresses such as chilling. We tested the hypothesis that a high percentage of blue light induces the accumulation of antioxidants and that this effect depends on the photosynthetic photon flux density (PPFD, 400–700 nm). The effect may be more pronounced at a lower PPFD. We investigated the changes in primary and secondary metabolites of basil in response to the percentage of blue light (9, 33, 65, and 100%) applied either as a 5-day End-Of-Production (EOP) treatment or continuous throughout the growth cycle in the green cv. Dolly. We also studied if the response to the percentage of blue light (9 or 90%) was dependent on the total PPFD (100 or 300 μmol m–2 s–1 PPFD) when applied as a 5-day EOP treatment in the green cv. Dolly and the purple cv. Rosie. For both green and purple basil, it was found that the percentage of blue light had little effect on the levels of antioxidants (rosmarinic acid, total ascorbic acid, total flavonoids, and total anthocyanins) at harvest and no interactive effect with PPFD was found. Antioxidants generally decreased during postharvest storage, wherein the decrease was more pronounced at 4 than at 12°C. Chilling injury, as judged from a decrease in Fv/Fm values and from the occurrence of black necrotic areas, was not affected by the percentage of blue light. Particularly, chilling tolerance in the purple cultivar was increased in plants grown under higher PPFD. This may be related to the increased levels of soluble sugar and starch in leaves from high PPFD treated plants.